Fetomaternal outcomes in vaginal discharge during pregnancy: A prospective comparative study - Bansal P; Jain S; Singh P; Goel N; Dahiya P (Asian Journal of Medical Sciences, 2024)
Background: Vaginal discharge (VD) is a common symptom in women during the reproductive period, especially during pregnancy. Pathological VD during pregnancy is an important public health concern because it has a sociopsychological impact on women and influences fetomaternal outcomes. Aims and Objectives: The study aims to estimate the prevalence of pathological discharge in pregnant women. The study also focuses on the demographic profile and various risk factors associated with pathological VDs and their consequences on fetal and maternal health. Materials and Methods: A prospective observational study was conducted in the Department of Obstetrics and Gynecology in a tertiary care center in Northern India. A total of 150 pregnant women with complaints of VD in the second and third trimesters with confirmation on speculum examination were recruited and evaluated for the etiology of discharge. Patients were followed until delivery and data regarding fetomaternal outcomes was collected. Results: The prevalence of pathological VD among enrolled women was 39.33% and various etiologies were candidiasis (15.33%), bacterial vaginosis (10.66%), aerobic vaginitis (8.67%), and trichomoniasis (4.67%). These infections were significantly related to pre-term delivery and pre-term pre-labor rupture of membranes. Furthermore, the incidence of prematurity, and low birth weight neonates requiring neonatal intensive care unit care was significantly high in babies born to mothers with pathological VD. Conclusion: Vaginal infections affect both maternal and neonatal health, thus, increasing the likelihood of poor perinatal outcomes. Hence, we propose that routine screening for pathological VD for all pregnant women should be introduced into standard antenatal care.